Estudio epidemiológico de sucesos traumáticos, trastorno de estrés post-traumático y otros trastornos psiquiátricos en una muestra representativa de Chile - Pérez Benítez, Carlos I. (2009)
In the last decade, our understanding of posttraumatic stress disorder (PTSD) has progressed from studies of war veterans and specific disaster victims to studies that examine the epidemiology of PTSD in the United States (USA) population. Epidemiologic data on PTSD in developing countries is an understudied area with the majority of studies were developed in the USA and other developed countries. Of the few epidemiological surveys undertaken in other countries, most of them have focused its interest on the prevalence rates of PTSD and its risk factors for following specific traumatic events. Besides increasing the international normative and descriptive data base on PTSD, an examination of prevalence rates and risk factors for PTSD in a socio-political and cultural context (that is markedly different to established market economies) can deepen our understanding of the phenomenology and determinants of PTSD. Although many psychiatric diagnoses can be related with previous traumatic experiences, PTSD has been identified as a disorder that requires a previous traumatic exposure for its diagnosis. A growing literature strongly suggests that early exposure to traumatic events disrupts crucial normal stages of childhood development and predisposes children to subsequent psychiatric sequelae. A series of epidemiological studies has demonstrated that childhood sexual abuse is associated with a range of psychiatric disorders in adulthood that includes mood, anxiety, and substance use disorders, even after adjusting for possible confounds, such as family factors and parental psychopathological disorders or other childhood adversities. There is little evidence of diagnostic specificity of childhood sexual abuse, although a consistent finding has been that alcohol and drug disorders are more strongly related to childhood sexual abuse than other psychiatric disorders. Other forms of childhood traumas have been less well studied. This article reviews the findings of an epidemiological study that took place in Chile and examined prevalence rates of PTSD, traumatic events most often associated with PTSD, comorbidity of PTSD with other lifetime psychiatric disorders, gender differences in PTSD as well as trauma exposure in a representative sample of Chileans. This article also reported a comparison of prevalence rates of various psychiatric disorders among persons who reported the first trauma during their childhood, those who reported the first trauma during their adulthood, and those with no trauma history. The study was based on a household-stratified sample of people defined by the health service system to be adults (aged 15 years and older). The study was designed to represent the population of Chile. This analysis is limited to three geographically distinct provinces, chosen as being representative of the distribution of much of the population. The interviews were administered to a representative sample of 2390 persons aged 15 to over 64 years. The measures used were the DSM-III-R PTSD and antisocial personality disorder modules from the Diagnostic Interview Schedule and modules for a range of DSM-III-R diagnoses from the Composite International Diagnostic. Traumatic events were categorized into one of 11 categories: military combat, rape, physical assault, seeing someone hurt or killed, disaster, threat, narrow escape, sudden injury/ accident, news of a sudden death or accident, other event (e.g. kidnapping, torture), or other experience. The translation into Spanish was conducted using the protocol outlined by the World Health Organization. The interviewers were all university students in their senior year studying social sciences. Taylor series linearization method was used to estimate the standard errors due to the sample design and the need for weighting. The analysis was conducted using procedures without replacement for non-respondents. The region, province, comuna, and district selected were used as the defined strata. Logistic regression with the corresponding 95% confidence interval was used to examine associations among PTSD, demographic risk factors, and trauma type. To examine whether the association between PTSD and gender could be explained by other risk factors, multivariate logistic regression analyses were also conducted. The first analysis found that the lifetime prevalence of PTSD was 4.4% (2.5% for men and 6.2% for women). Among the traumatic events, rape was most strongly associated with PTSD diagnosis. Among those exposed to traumas, women were significantly more likely to develop PTSD than men, after controlling for assaultive violence. The second analysis revealed that exposure to a lifetime trauma was associated with a higher probability of psychiatric morbidity in comparison with no trauma exposure. Traumas with childhood onset were significantly related to lifetime panic disorder, independent of number of lifetime traumas and demographic differences. This revealed that women had more probabilities than men of developing PTSD once they are exposed to trauma, independent of previous traumas, experiences of sexual assault, other violent experiences or level of education. Some authors have proposed that women have a higher vulnerability than men to develop PTSD and that there are sex differences in brain morphology, in the social interpretation of trauma, or/and in the peritraumatic dissociative experience. Although many theories have been proposed to explain this gender difference in PTSD, more research is needed to evaluate them empirically. This study highlights the importance of investigating the prevalence of PTSD, the patterns of comorbidity of PTSD, as well as gender differences of PTSD in non-English speaking countries. Although Chile has a different historical and socio-cultural context with respect to other countries in which the epidemiology of PTSD has been examined, in general, this study achieved similar results as those found in other studies. The results showed that PTSD is not an uncommon psychiatric illness, it is associated with a high degree of psychiatric comorbidity, it is more likely to predate other psychiatric disorders. Also, the results showed that men are more likely to be exposed to traumas than women, women are more likely than men to develop PTSD, and that PTSD is associated with relatively high treatment utilization. However, compared to another country in Latin America, such as Mexico, Chile has a lower prevalence of PTSD and trauma exposure, which may due to socio-economic factors, such as less inequity between the wealthy and the poor and less violence, crime, and poverty in Chile than Mexico. These studies also suggest that traumatic events that occur in childhood are related to specific disorders rather than those that occurred later in life. Individuals with childhood interpersonal trauma exposure are more likely to suffer from lifetime panic disorder, agoraphobia or PTSD compared to those who experience interpersonal trauma as an adult. However, research should examine the specificity of these disorders in relation to various types of childhood traumas. Limitations of the current study include the use of lay interviewers who, despite acceptable levels of reliability and validity, may be less accurate than clinicians as interviewers. Also the retrospective recall of lifetime disorders is likely to be less accurate than a more recent time frame. The sample used in this study does not show nation wide perspective, because the Southern portion of the country which includes much of the indigenous population was excluded. This study, like most epidemiological studies, did not use an-depth or validated index of trauma, which may have diluted findings. Since this study was cross-sectional, a direct cause-effect relationship cannot be assumed between trauma exposure and subsequent disorders.